Integrated physics-based approach for the reliability prediction of thermal systems. (4th April 2011) - Al-Habahbeh, O.M.; Aidun, D.K.; Marzocca, P.; Lee, H.
A broad reliability prediction method that can deal with complex thermo-fluidic systems is introduced. The procedure provides an engineering tool by integrating multiple computational packages that enable the simulation of a wide array of systems, especially those involving physics interactions such as fluid flow and solid medium. Computational Fluid Dynamics, Finite Element Method, Monte Carlo Simulation and fatigue analysis tools are integrated within this physics-based reliability prediction approach. The complete procedure is demonstrated using a simple example, and then validated using boiler pipes experimental data. CFD simulations are used to determine the convective terms necessary for the transient FEM thermal analysis. The thermal analysis provides maximum thermal stress whereby the fatigue life of the component is evaluated. As a result of input parameters uncertainty, the expected life will be in the form of a Probability Density Function, which enables the calculation of the reliability of the component.